Prognostic Role of Soluble Programmed Death Ligand 1 in Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Liao, Guixiang; Zhao, Zhihong; Qian, Yuting; Ling, Xiean; Chen, Shanyi; Li, Xianming; Kong, Feng-Ming (Spring) (Frontiers in Oncology, 2021)
Objective The objective of this study was to explore whether soluble programmed death ligand 1 (sPD-L1) is a potential prognostic biomarker in patients with non-small cell lung cancer (NSCLC). Methods A comprehensive search of electronic databases was carried out. Original studies with inclusion of sPD-L1, progression-free survival, and overall survival in NSCLC were eligible. The primary endpoints were overall survival and progression-free survival. Hazard ratios (HRs) and 95% confidence intervals (CIs) were applied for data analysis. Results Eight studies involving 710 patients with NSCLC were included in the analysis. A pooled data analysis revealed that high levels of sPD-L1 were correlated with poorer overall survival (HR = 2.34; 95% CI = 1.82–3.00; P < 0.001) and progression-free survival (HR = 2.35; 95% CI = 1.62–3.40, P < 0.001). A subgroup analysis revealed that high levels of sPD-L1 were correlated with poor overall survival in patients treated with immunotherapy (HR = 2.40; 95% CI = 1.79–3.22; P < 0.001). Conclusion This pooled analysis of published data suggests that sPD-L1 may serve as a readily available biomarker for survival in NSCLC patients treated with ICI based treatment. Prospective studies with well-designed standard assessment methods should be conducted to validate the prognostic role of sPD-L1 in NSCLC. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021283177.